Apresentação do Dossiê "Esporte e tecnologia: pensando corpos, práticas e artefatos" - Gonçalves, Michelle Carreirão; Camargo, Wagner Xavier de (PerCursos, 2025)
Apresentação do Dossiê "Esporte e tecnologia: pensando corpos, práticas e artefatos"